NON-SPECIFIC MESENTERIC LYMPHADENITIS IN CHILDREN (LITERATURE REVIEW) - E. A. Sologub; O. V. Karaseva; A. G. Timofeeva (Union of pediatricians of Russia, 2013)
A problem of timely diagnostics and management tactics of acute non-specific mesenteric lymphadenitis in children has not been settled yet, as there is no common opinion of its etiology and pathogenesis. This disease is of practical interest for pediatricians and pediatric surgeons, as the acute mesenteric lymphadenitis's clinical presentation gives an "acute abdomen" symptomatic complex; this determines its importance in differential diagnosis with acute appendicitis. The article gives a literature review on this issue.